129k views
4 votes
Follow the process of completing the square to solve x2 = -4x + 3.

User Li Juan
by
5.5k points

1 Answer

4 votes

Answer:

x = - 2 ±
√(7)

Explanation:

Given

x² = - 4x + 3 ( add 4x to both sides )

x² + 4x = 3

To complete the square

add (half the coefficient of the x- term)² to both sides

x² + 2(2)x + 2² = 3 + 2²

(x + 2)² = 3 + 4 = 7 ← take the square root of both sides

x + 2 = ±
√(7) ← subtract 2 from both sides

x = - 2 ±
√(7) ← exact values

User Robsonsanches
by
5.9k points